Long Term Evaluation Of Maxillary Growth After ‘The Non Denuded Palatoplasty’ Technique - Kreshanti, Prasetyanugraheni; Handayani, Siti; Rachmasari, Maulina; Pancawati, Julieta; Susanto, Amila Jeni; Wangge, Grace; Indania, Alita (Jurnal Plastik Rekonstruksi, 2018)
Background : Conventional Two Flap Palatoplasty technique will produce lateral defects without any periosteal coverage. These denuded lateral defects are prone to contamination and infection. These will result in wound contraction, scar formation and maxillary growth impairment. In 2011, we studied “The Non Denuded Palatoplasty” technique. This technique precipitated the epithelialization process of the lateral defects. Faster epithelialization is expected to decrease wound contraction and good maxillary growth. Method : This is a case control study to compare the maxillary growth of 2 groups consists of unilateral cleft lip and palate patients repaired with “The Non Denuded Palatoplasty” technique and Conventional Two Flap Palatoplasty. The outcome will be evaluated from cephalometry and the dental cast for each patient is evaluated using GOSLON YARDSTICK method. Data will be analyzed using SPSS version 20. Result : A total of 4 patients in The Non Denuded Palatoplasty group and 10 in the Conventional Two Flap Palatoplasty. The cephalometric SNA, SNB and ANB point showed Class III skeletal jaw relationship or deficient maxilla. Meanwhile the GOSLON yardstick type III are the most common GOSLON on both group with good inter-ratter reliability (p=0.839) based on Mann Whitney test. In these study, there was no correlation between cephalometric variables with GOSLON score. Conclusion: Our results showed that modification (The Non Denuded Palatoplasty) technique made no statistically significant difference to the maxillary growth. However this study has several limitations, one of which being the small sample size due to family, social and other factors that are beyond the control of the investigating team. Also the evaluation was conducted in patients aged 7-9 years, hence the result of this study is not the final outcome. Keywords: maxillary growth evaluation, cephalometry, Goslon Yardstick, two flap palatoplasty